Eschato-praxis and accountability: A study of Neo-African Pentecostal movement in the light of prosperity gospel - Adedibu, Babatunde A.; Igboin, Benson O. (Verbum et Ecclesia, 2019)
The quest for accountability in Christian theology is both immediate and ultimate. This, thus, suggests that individuals and groups within spiritual and secular spaces subscribe to some form of immediate and ultimate probity and accountability assessment. Given this, it would be argued that accountability has eschatological implications on neo-African Pentecostalism – the thrust of this study. Through the gristmill of eschato-praxis – a theory and belief that paradisiac bliss can be enjoyed on earth by Christians as a foretaste of its full and eternal enjoyment in heaven, a practice that has suffused neo-African Pentecostalism, which is largely manifest in luxury and quest for materiality – it would be argued why and how accountability must be countenanced into the practice of the neo-African Pentecostals, also as a foretaste of the ultimate demand and event. This study utilises descriptive and theological approaches to eschato-praxis and accountability within the neo-African Pentecostal movement.
free
Keywords: Africa.; Eschatology – Christianity; Pentecostalism; Prosperity theology; Responsibility